2016
DOI: 10.1016/j.ajme.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A study of serum magnesium, calcium and phosphorus level, and cognition in the elderly population of South India

Abstract: Introduction: Different studies have shown the role of micro and macronutrients on cognitive function. Macronutrients have been involved in many metabolic activities of the body including oxidation and reduction reactions in the central nervous system. This involvement of macronutrients in the activities of central nervous system indicates its role in cognition. The present study is designed to know the role of macronutrients and its relation with cognition by using biological samples. Materials and methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
(25 reference statements)
4
7
0
1
Order By: Relevance
“…It is consistent with other studies like Vural et al23 , Basheer et al24 .The cut off value of serum Magnesium was set at 2.15 mg/dl. In this study, below cut off value in case group was 64.7% and in control group was 14.7%.…”
supporting
confidence: 87%
“…It is consistent with other studies like Vural et al23 , Basheer et al24 .The cut off value of serum Magnesium was set at 2.15 mg/dl. In this study, below cut off value in case group was 64.7% and in control group was 14.7%.…”
supporting
confidence: 87%
“…In general, these associations are in line with previous studies showing associations between CMR and age‐related neurodegenerative diseases and cognitive decline. For example, higher serum phosphate, an element filtered by the kidney, is associated with increased risk of incident dementia (Li, Xie, Bowe, Xian, & Al‐Aly, 2017), and risk of brain hemorrhage (Yamada et al, 2016), while low serum phosphate level is associated with cerebral β‐amyloid deposition (Park et al, 2017), increased risk of brain infarction in hemodialysis patients (Yamada et al, 2016), and lower composite score in relation to cognitive function (Basheer, Pradeep Kumar, Sreekumaran, & Ramakrishna, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that women with calcium supplements had higher risk of developing dementia than women without calcium supplementation ( Kern et al, 2016 ). A cross sectional study in 337 subjects in India indicated that increased calcium level could increase the cognitive score ( Basheer et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%